Construction and validation of measurement instruments in the field of health. Literature Review - Rojas Apaza, Zenaida (2022)
The process of construction and validation of measurement instruments in the field of health is a complex issue that includes various stages, the existing information on this methodological process is scattered and unclear. The objective of this article is to synthesize and propose recommendations based on the scientific literature on an adequate methodological process for the construction and validation of measurement instruments in the field of health. An exhaustive review of the literature was carried out in databases such as Medline, Scielo, Science direct and Google Schoolar between 1994 and 2020, related to the construction and validation of measurement instruments. 62 articles were obtained, after reading and exclusion, 34 articles considered adequate to meet the stated objectives were selected. Based on the information found, the stages for an adequate construction and validation process are described, the psychometric properties such as validity and reliability are presented, in addition to the various statistical tests used to guarantee a valid and reliable instrument.